ANALISIS KETERAMPILAN BERPIKIR KREATIF MAHASISWA DALAM MENYUSUN LAPORAN KEGIATAN PRAKTIKUM BOTANI TUMBUHAN TAK BERPEMBULUH - ERMAYANTI ERMAYANTI; Didi Jaya Santri (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2020)
This research aims to obtain information about students' creativity in arranging the results of practicum activities in the botany of non-vascular plant course.  This research was used descriptive design. The participants of this study were third semester biology education students (n=25) at a state university in Sumatera, Indonesia. The student was taken botany of non-vascular plant course. The instruments used in this research were performance instruments that measured students' creative thinking skills, questionnaires and observation guidelines that have been developed. The performance instrument used contains several indicators, namely: fluency, flexibility, originality dan elaboration. The data of creative thinking skills were processed by calculating the percentage (%) for each indicator and categorized into four levels (very creative, creative, quite creative and less creative). The results showed that students' creative thinking ability in compiling reports on the practicum activities is (2.68) classified into creative categories with an average of each indicator that are: fluency (3.06); flexibility (2.96), originality (2.95), and elaboration (1.76). The results show that the average student has good creative thinking skills in compiling reports of the practicum activities of botany of non-vascular plant course